Density variability in radial direction and in growth ring of Pinus caribaea var. hondurensis from plantations of 25 years old - Márquez-Carrero, Gabrialy (2022)
This paper deals about air-dry density in wood from six trees of Pinus caribaea var. hondurensis (Sénécl) W. Barret & Golfari (Pinaceae) from 25 years old plantations growing in Uverito (Monagas state, Venezuela). Samples were taken in three positions of cross section: near of pith (all growth ring), middle point (sample for early wood and sample for late wood) and near of cambium (all growth ring). Density was obtained according DIN 52-182. Density grows from pith to cambium (0,595 near of pith; 0,681 in middle zone and 0,820 g/cm³ near of cambium). In late wood, we found higher values in air-dry density (0,806 g/cm³) in comparation with early wood (0,557 g/cm³). According Tukey test (α = 0,01), there are significatives differences between air-dry density in pith zone-cambial zone and between early and late wood.